Fast transient simulation of pinceti surge arrester model on a transmission line using ATP Software - Muhamad, Yusof (2015)
Lightning is one of the main causes of overvoltage on power system. Over voltages problem at the transmission line can cause flashover voltage at the insulator string, power system disturbances and transformer failure. To prevent of insulator string and equipment of the power system from damaging effect by lightning overvoltage, metal oxide surge arrester is installed at overhead line in parallel with insulator string. Due to metal oxide surge arrester have dynamic behaviour, this arrester can be simulated using non-linear resistor. Therefore Pinceti model is proposed to simulate using Alternative Transient Program (ATP) software. Several procedures have been following to calculate Pinceti arrester model parameters so that compatible with 132kV overhead transmission line system. Tested result by simulation is compared with the manufacturer arrester datasheet to evaluate accuracy of Pinceti model before installed arrester at 132kV transmission line model. Pinceti model are installed at several locations on the transmission line model to evaluate the level of effectiveness and capabilities to reduce the level of overvoltage across insulator string and to ensure lightning overcurrent draws to ground totally.